Perlindungan Hukum Terhadap Pemegang Hak Desain Industri Atas Kesamaan Produk Desain Industri (Studi Putusan Nomor 583 K/Pdt.Sus-HKI/2021) - Devi Octaviani; Septi Indrawati; Muhammad Alfian (Suara Edukasi Hukum, 2026)
Devi Octaviani, "Legal Protection for Industrial Design Rights Holders for the Similarities of Industrial Design Products." Legal Study Program, Faculty of Psychology, Law and Social Sciences, Muhammadiyah University Purworejo, 2026. This research aims to analyze the form of legal protection for industrial design rights holders in Indonesia based on Law Number 31 of 2000 concerning Industrial Design and examine the judge's considerations in Decision Number 583 K/Pdt.Sus-HKI/2021 regarding the application of the principle of novelty. Industrial Design as part of Intellectual Property Rights has an important role in the business world because it provides aesthetic value and competitiveness of a product. Therefore, legal protection for industrial designs is essential to guarantee legal certainty and justice for rights holders. The type of research used is normative juridical research with a statutory approach and a case approach.  The research results show that legal protection for industrial design rights holders is provided through a constitutive registration system (first to file), which includes preventive and repressive protection. Preventive protection is realized through registration of industrial designs at the Directorate General of Intellectual Property, while repressive protection is provided through a lawsuit mechanism at the Commercial Court if a violation occurs. In Decision Number 583/Pdt.Sus-HKI/2021, the Supreme Court canceled the Defendant's industrial design because it did not meet the element of novelty as regulated in Article 2 of Law Number 31 of 2000. The panel of judges considered that the registered design had been previously disclosed and used by another party before the date of receipt of the application, so it was not worthy of legal protection. This decision confirms that the principle of novelty is an absolute requirement for granting industrial design rights and is the main basis for resolving industrial design disputes in Indonesia.